2012
DOI: 10.1111/j.1365-2133.2012.10822.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical temperature threshold measurement for cold urticaria: a randomized controlled trial of H 1 ‐antihistamine dose escalation

Abstract: Measurement of CTT allows for individualized risk management and therapy in patients with cold urticaria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 8 publications
3
50
0
3
Order By: Relevance
“…Two previous studies have shown a decrease in the CTT after a therapeutic intervention in ACU (19,34). Mlynek et al (19) showed a correlation between decrease in CTT and clinical improvement of the disease.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Two previous studies have shown a decrease in the CTT after a therapeutic intervention in ACU (19,34). Mlynek et al (19) showed a correlation between decrease in CTT and clinical improvement of the disease.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, none of these non-standardized and subjective methods of assessing clinical response to treatment appear to be reproducible. Siebenhaar et al (17) describe the objective measurement of disease activity and the response to therapeutic interventions using electronic TempTest ® equipment (34). This reli able method enables the precise and accurate control of treatment effects on the basis of monitoring threshold temperatures.…”
mentioning
confidence: 99%
“…2,4,5,13 However, reduction of urticarial symptoms in many patients requires antihistamines at high doses, up to 4 times the standard dose. 4,5,[13][14][15] In our series, 85% of the patients who were treated with antihistamines showed significant clinical improvement. Rates of satisfactory clinical response with antihistamines ranged from 60% to 70% in previous series.…”
Section: Discussionmentioning
confidence: 98%
“…An example is chronic urticaria, a "non-anaphylactic" allergic disease, with enormous life-threatening potential. 57 In humans, an observation period of 6-8 h for patients with respiratory symptoms and 12-24 h for patients with hypotension and collapse is recommended due to possible biphasic reactions, but should be assessed on a case-by-case basis. 11,12 An anaphylaxis veterinary review recommended 3 days, but this was not based on clinical data from studies.…”
Section: Discussionmentioning
confidence: 99%